2007
DOI: 10.1016/s0140-6736(07)60109-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3-year folic acid supplementation on cognitive function in older adults in the FACIT trial: a randomised, double blind, controlled trial

Abstract: Folic acid supplementation for 3 years significantly improved domains of cognitive function that tend to decline with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
482
1
15

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(512 citation statements)
references
References 38 publications
14
482
1
15
Order By: Relevance
“…In a 3-year study of the elderly, a daily intake of 800 mg of oral folic acid significantly improved those domains of cognitive function that deteriorate with age. 23 …”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…In a 3-year study of the elderly, a daily intake of 800 mg of oral folic acid significantly improved those domains of cognitive function that deteriorate with age. 23 …”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Folic acid consumption, with or without vitamin B 12 , may help prevent cognitive impairment in the elderly, possibly through lowering plasma homocysteine levels (12,13) . A 3-year randomised double-blind placebocontrolled trial involving >800 older adults (aged 50-70 years, all vitamin B 12 replete) in The Netherlands has found that supplements of 800 mg folic acid over 3 years improve cognitive function (14) . Improvements in this trial were found to involve domains of cognitive function associated with ageing and these changes were shown to be associated with reductions in homocysteine (14) .…”
Section: Cognitive Functionmentioning
confidence: 99%
“…One of the relevant environmental factors seems to be food. There is a growing awareness that food may play a role in determining not only our physical well-being, but also our behaviour and cognitive functioning [6][7][8]. The role of food in ADHD has been investigated since 1985 in several restricted elimination diet (RED) studies.…”
mentioning
confidence: 99%